2016
DOI: 10.1016/j.lindif.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Separating the effects of ethnicity and socio-economic status on sleep practices of 6- to 7-month-old infants

Abstract: Infant sleep undergoes significant re-organization throughout the first 12 months of life, with sleep quality having significant consequences for infant learning and cognitive development. While there has been great interest in the neural basis and developmental trajectories of infant sleep in general, relatively little is known about individual differences in infant sleep and the socio-economic and cultural sources of that variability. We investigated this using questionnaire sleep data in a large, unique mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 26 Unfortunately, direct evidence on relevant infant care practices is very limited: for example, a comparison of 20 Afro-Caribbean with 33 White British babies in East London found that the Afro-Caribbean babies were more likely to share the parental bed and to ‘prefer’ front sleeping, but numbers were very small, the participating parents were volunteers and more than one preferred sleep position could be reported, with no indication of frequency. 27 …”
Section: Discussionmentioning
confidence: 99%
“… 26 Unfortunately, direct evidence on relevant infant care practices is very limited: for example, a comparison of 20 Afro-Caribbean with 33 White British babies in East London found that the Afro-Caribbean babies were more likely to share the parental bed and to ‘prefer’ front sleeping, but numbers were very small, the participating parents were volunteers and more than one preferred sleep position could be reported, with no indication of frequency. 27 …”
Section: Discussionmentioning
confidence: 99%
“…In Canada, First Nation mothers are more likely to cosleep than White mothers (Bartick & Tomori, 2019). Similarly, in the United Kingdom, Pakistani and Bangladeshi families of any SES were much more likely to cosleep than White British families (Ball, 2012; Gantley et al., 1993; Tomalski et al., 2016), and in the Netherlands, Carribean mothers were more likely to cosleep than Dutch mothers (Luijk et al., 2013). In Thailand, minority Christian and Muslim mothers were more likely than Buddhist mothers to cosleep (Anuntaseree et al., 2008), and in New Zealand, Maori mothers have high rates of cosleeping (Bartick & Tomori, 2019; Rigda et al., 2000).…”
Section: The Sociocutural View Of Infant Sleepmentioning
confidence: 96%